Analisis Meta Business Suite Sebagai Media Promosi Untuk Meningkatkan Kunjungan Dan Penjualan Di Restoran Copas Suburban Dining Gading Serpong, Kabupaten Tangerang - Siti Umriah; Joko Prasetiyo (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the utilization of Meta Business Suite as a promotional medium to increase customer visits and sales at Copas Suburban Dining Restaurant, Gading Serpong, Tangerang Regency. This research is motivated by the increasing competition in the culinary business and the important role of social media as an effective digital marketing tool. Meta Business Suite is used by the restaurant management to manage promotional content, schedule posts, manage advertisements, and analyze promotional performance through Instagram and Facebook platforms. This research uses a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews with management and marketing staff, documentation, and SWOT analysis. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The first study showed that the use of Meta Business Suite had a positive impact on increasing awareness, engagement, and promotional reach at Copas Suburban Dining Restaurant. The second study found that promotional effectiveness was not fully optimal due to obstacles such as changes in social media algorithms, limited advertising budgets, and increasingly fierce business competition. The third study concluded that Meta Business Suite plays a significant role as a digital promotional medium, but requires a planned strategy and ongoing evaluation to optimally increase visits and sales